Laccase Inhibition by Mercury: Kinetics, Inhibition Mechanism, and Preliminary Application in the Spectrophotometric Quantification of Mercury Ions - J. Juárez-Gómez; E. S. Rosas-Tate; G. Roa-Morales; P. Balderas-Hernández; M. Romero-Romo; M. T. Ramírez-Silva (Journal of Chemistry)
The noncompetitive inhibition of laccase by mercury ions is reported, in particular focusing their effect over the enzyme catalytic activity. The enzymatic kinetics were obtained for different substrates (caffeic acid, gallic acid, and catechol), where caffeic acid displayed the greatest enzymatic activity. The laccase inhibition by mercury ions permitted to establish the inhibition effect through a mixed model (that actually displayed a behavior closer to that of the noncompetitive inhibitors) when evaluated by means of UV-Vis spectrophotometry, using caffeic acid as an electron donor. A mercury concentration of 2 mM led to 35% enzymatic inhibition after only a 2-minute incubation period. This method was used for quantification of mercury ions in aqueous solution, showing a detection limit of 15 ± 1 ppm. Therefore, this work presented a novel perspective for the determination of the toxic Hg(II) ions that can be readily implemented into environmental remediation methods.